Onde dois horizontes se encontram: a dessacralização da violência no teatro de Eurípides e de Sérgio Roveri - Fiuza, Bianca de Franceschi (2023)
Having been a part of mythic narratives long before Euripides wrote his tragedy, the myth of Medea was the object of many reinterpretations throughout Western history. But Euripides was, as far as we know, the first to charge Medea with revenge-motivated filicide. In the Greek poet’s text, she is a wicked woman who gets carried away by vengeful desire upon finding that her husband had betrayed her. From that point on, violence and filicide are evoked whenever her name is mentioned. Likewise, the 2014 play Medeia: 1 verbo, by the Brazilian playwright Sérgio Roveri, also deals with the topics of violence and filicide. But Roveri, who revisits Euripides’ tragic play, proposes a new look on the character. Speaking from a contemporary stance, his text differs significantly from Euripides’ Medea. Nonetheless, it is surely possible to identify points of concurrence between both plays. Drawing from concepts developed by Jauss, a reception aesthetics theorist, we seek to comprehend in what way Euripides’ tragedy is updated by the Brazilian playwright’s own play. In addition to that, as violence is present as a theme in both texts, we resort to René Girard, an author who studied the phenomenon of violence in human history. With his studies as a foundation, our discussion focuses on the different expectation horizons out of which both Euripides and Roveri have created their texts. This investigation also relies on texts conceived in and around the fields of critical theory and social history by authors such as Kitto, Jaeger, Hauser, Baumgarten, Brandão, Rosenfeld, Szondi, etc.